A Nd:YAG Laser-Pumped Hydrogen Raman Shifter with Capillary Waveguide - Torres, Maria Leilani; Cadatal, Marilou; Garcia, Wilson (Science Diliman: A Journal of Pure and Applied Sciences; Vol 17 No 1 (2005), 2007)
Operation of a 355/532 nm Nd:YAG laser-pumped hydrogen Raman shifter with capillary waveguide (CWG) is demonstrated. For both pump wavelengths, more laser lines are generated using the Raman shifter with CWG compared to a conventional Raman shifter. Both 355 and 532 nm pumps showed a 60% decrease in threshold power for the generated first Stokes (S1) Laser line. The 355 nm-pumped Raman shifter with CWG generated S1 at 2.1 mW pump power at a hydrogen pressure of 1.38 MPa. On the other hand, for the 532 nm pumped waveguide Raman shifter at a hydrogen pressure of 1.72 MPa, the threshold power for S1 is at 8.3 mW. In addition, an improvement of the output powers is observed for the Stokes and anti-Stokes generated by Raman shifter with CWG.